2020
DOI: 10.2196/18343
|View full text |Cite
|
Sign up to set email alerts
|

A Social Media–Based Support Group for Youth Living With HIV in Nigeria (SMART Connections): Randomized Controlled Trial

Abstract: Background Youth living with HIV (YLHIV) enrolled in HIV treatment experience higher loss to follow-up, suboptimal treatment adherence, and greater HIV-related mortality compared with younger children or adults. Despite poorer health outcomes, few interventions target youth specifically. Expanding access to mobile phone technology, in low- and middle-income countries (LMICs) in particular, has increased interest in using this technology to improve health outcomes. mHealth interventions may present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(100 citation statements)
references
References 47 publications
(36 reference statements)
3
96
0
1
Order By: Relevance
“…The majority of studies were conducted in the United States (n = 18, 60%), with the remainder of studies done in Uganda (n = 4) [63][64][65][66][67], Thailand (n = 3) [68][69][70][71], Zimbabwe (n = 2) [72,73], Nigeria (n = 1) [74], South Africa (n = 1) [75] and Zambia (n = 1) [76]. Most studies (n = 26, 86.7%) used an individually randomized controlled trial design to evaluate the intervention, whereas fewer (n = 4, 13.3%) used cluster randomization with families or clinic sites as the unit of randomization (Table 1) [63,67,71,72,77].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies were conducted in the United States (n = 18, 60%), with the remainder of studies done in Uganda (n = 4) [63][64][65][66][67], Thailand (n = 3) [68][69][70][71], Zimbabwe (n = 2) [72,73], Nigeria (n = 1) [74], South Africa (n = 1) [75] and Zambia (n = 1) [76]. Most studies (n = 26, 86.7%) used an individually randomized controlled trial design to evaluate the intervention, whereas fewer (n = 4, 13.3%) used cluster randomization with families or clinic sites as the unit of randomization (Table 1) [63,67,71,72,77].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Four studies involved peer implementers, in some cases relying on professional support to implement interventions [72,73,76,93]. Five interventions were delivered by lay counsellors or facilitators [74,79,86,87,94,95]. Additionally, five interventions had no delivery personnel involved and were delivered by digital means only (one of these was delivered in a hybrid clinicaldigital setting as described above) [65,66,82,84,85].…”
Section: Personnelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of HIV/AIDS prevention, eHealth communication tools improve health outcomes across the HIV care continuum, which include diagnosis of HIV infection; linkage, engagement, retention in HIV care; and achieving viral suppression [ 4 , 5 ]. Recent studies [ 6 - 14 ] have shown how social media and technologies such as avatar-led and smartphone games can be leveraged to prevent the spread of HIV infection and sexually transmitted diseases, as well as improve HIV-related health outcomes such as diagnosis of HIV infection; linkage, engagement, retention in HIV care; and medication adherence.…”
Section: Introductionmentioning
confidence: 99%